Teknik MPPT Sederhana Menggunakan Fuzzy-PI untuk Mencapai Daya Output yang Efisien - Akbar, Bagus Alfaridzi Akbar; Wahjono, Endro; Dwi Murdianto, Farid Dwi Murdianto (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
Solar panels are one of the renewable and environmentally friendly sources of electrical energy. Renewable energy at this time is often discussed, because non-renewable energy at this time has caused many negative effects on the earth. In utilizing solar panel electrical energy sources is fairly difficult, because to be at its best performance, solar panels must be at a certain irradiation and temperature. But in fact irradiation and temperature always change so that the power produced changes so that the power output is not optimal. Therefore, a tool is needed that is able to find the maximum power point automatically at any irradiation and temperature conditions, therefore in this study Maximum Power Point Tracking (MPPT) is proposed using the Fuzzy-PI method so that the power output produced can always be maximized. The proposed Maximum Power Point Tracking (MPPT) was tested through extreme irradiation and temperature changes and also compared to the Pmax value resulting in a Maximum Power Peak (MPP) accuracy of 94.69 %.